Podcasting for public libraries in Egypt: a strategic vision - Heba Nasr (Cybrarians Journal, 2025)
This comprehensive study investigates the potential of electronic audio broadcasting (podcasting) within Egyptian public libraries, with a specific focus on planning its implementation and creating a radio system. It explores the current landscape of podcast services in both foreign and Arab public libraries, aiming to identify criteria for evaluating these services and the necessary skills for information specialists to manage podcast platforms. The research proposes a structured plan for establishing an audio broadcasting channel within the Egyptian public library system, drawing insights from existing models and outlining the required resources and implementation phases to enhance information access and engagement for users. The study ultimately recommends integrating podcasting into library services, advocating for professional development and new job roles for librarians in this evolving digital media landscape.